Kampanye Pemilu Dialogis untuk Pemilu 2009 - Wardhani, Andy Corry (FIkom Unisba, 2008)
Political campaign on 2004 was marked by monologue campaigns in the form of mass rally and mass gathering. Information dissemination for the mass was carried out by placing signpost, banners, and pamphlets depicting party’s symbol. This kind of campaign belonged to one way communication. Both political party and political leaders were failed to gain feedback from the mass, whereas feedback reflected public’s needs and wishes. As consequences, monologue campaigns provide us with low quality campaign oriented toward figures, not their programs. Considering this, a dialogues form of campaign is offered for repairing ineffective political communication between party and people. Dialogical campaigns establish a two-way-communication between party and public, provide ways to clearly communicate problems surrounding the whole situation packaged with party’s point of view and its solutions. By conducting dialogical campaign which reflected a-two-way- communication, campaigners and policymakers would benefit from the exchange of public aspirations along the process.